PEMBATASAN PERJANJIAN LISENSI HAK ATAS KEKAYAAN NTELEKTUAL DALAM HUKUM PERSAINGAN USAHA - Putranti, Deslaely (Jurnal Yuridis, 2015)
The licensing agreement on intellectual property rights raises the exclusive rights in the form of a monopoly on intellectual property rights. The exclusive rights are abused by the holder or owner of the intellectual property rights to determine the license agreement that violates the principles of competition. Setting licensing restrictions in Article 50 letter b of UU No. 5/1999 is appropriate only where the article is just limiting the intellectual property rights that may arise in the future. Setting licensing restrictions should not only be governed by UU No. 5/1999 alone, but also governed by laws and regulations related to intellectual property rights continuously, so that theimplementation of the licensing agreement limitation becomes maximal.